Implementation of PjBL-STEM Learning to Improve Students' Higher Order Thinking Skills in Direct Current Electricity - Salmah, Ummi; Suwasono*, Purbo; Kurniawan, Robi; Swapno, S M Masfequier Rahman (Universitas Syiah Kuala, 2025)
Improving the quality of education is crucial in ensuring that students are equipped to adapt to rapid advancements in science and technology. This study aims to examine the effect of implementing a STEM-integrated project-based learning (PjBL) model on students higher-order thinking skills (HOTS). The research used a quantitative approach with a quasi-experimental method, employing a pretest-posttest non-equivalent control group design. The participants were 71 students from a school in Riau province, divided into an experimental class (35 students) and a control class (36 students). The results indicate that students in the experimental class achieved a good category of HOTS with an average posttest score of 61.90. A significant improvement was observed in the posttest scores across three HOTS indicators: analyzing, evaluating, and creating. The obtained N-gain score of 0.48 indicates a moderate level of improvement. Specifically, the average score for the analyzing (C4) domain increased to 68.73 (good), the evaluating (C5) domain reached 55.24 (fair), and the creating (C6) domain rose to 48.10 (fair). The results of the Mann-Whitney U test indicated a significant difference between the experimental and control groups (Asymp Sig 2-tailed = 0.000). Further analysis showed a moderate N-Gain score of 0.488 and a strong effect size (d = 0.76), confirming that the implementation of the PjBL-STEM model effectively enhanced students' HOTS in the topic of direct current electricity